Dysglycemia and Neurologic Outcome in Mechanically Ventilated Patients With Guillain-Barré Syndrome. Issue 3 (March 2019) - Polito, Andrea; Polito, Angelo; Bouchereau, Eléonore; Moneger, Guy; Ritzenthaler, Thomas; Annane, Djillali; Heming, Nicholas; Sharshar, Tarek
Abstract : Objectives: Acute respiratory failure is a frequent complication of Guillain-Barré syndrome, associated with high morbidity and mortality. Adjuvant treatments are needed to improve the outcome of Guillain-Barré syndrome. Since dysglycemia is a risk factor for development of axonal polyneuropathy in critically ill patients and since insulin therapy may be neuroprotective, we sought to explore the association between dysglycemia and neurologic status in Guillain-Barré syndrome patients. Design: Retrospective study. Setting: Single-center study. Interventions: All plasma levels of glycemia measured by enzymatic technique as well as capillary glycemia were collected in a cohort of mechanically ventilated Guillain-Barré syndrome patients. Insulin administration and dysglycemia were correlated to neurologic status at discharge defined by disability grade and arm grade. Measurements and Main Results: In a multivariate analysis, disability grade and arm grade at ICU discharge were independently and inversely correlated with mean blood glucose. Disability grade and arm grade did not correlate with any other dysglycemic variables or with insulin administration or length of stay. Conclusions: In the present study, we found that neurologic disability at ICU discharge correlated with dysglycemia in mechanically ventilated Guillain-Barré syndrome patients. These finding indicates that dysglycemia may delay motor recovery and impact the functional outcome of Guillain-Barré syndrome. Blood glucose control might be an adjuvant therapy for improving Guillain-Barré syndrome recovery.